Percurso histórico dos cursos de pós-graduação stricto sensu da Universidade Federal de Sergipe : lugar de formação para o magistério superior? - Dórea, Nívia Maria de Vasconcellos Couto (2019)
The academic and legal formulations for the training of higher education teachers through the stricto sensu post-graduate course of the Federal University of Sergipe - UFS, in the macro context of the Brazilian postgraduate course, is an object of study of this dissertation. Our perspective is its historic course of constitution as the highest level of Brazilian higher education, configured as a possible place of formation for the higher teaching. Therefore, this work aims to analyze, from a historical point of view, the place of teacher training in UFS postgraduate courses. In order to support the general objectives, we have specific objectives: to describe the emergency process and trajectory of UFS graduate programs; to show if these programs constitute a place of formation for the higher teaching; and characterize the elements indicative of this formation. To facilitate the theorization of research, and to assign contextual meaning to content analysis, we choose the terms space, place, and territory. Universities, through their stricto sensu postgraduate courses, constitute spaces that guarantee the possibility of formation for the higher teaching profession, but do not guarantee their concretization, that is, they do not guarantee to be a place where, in fact, the formation happens, and here arises the investigation of this work. Thus, we established as a selection criterion the 43 graduate programs of the Federal University of Sergipe Foundation - FUFSE, which were evaluated by CAPES in the quadrennium 2013-2016. The method of approach is quantitative-qualitative, exploratory, with the methodological resource of content analysis, where the data collected will come from bibliographic and documentary analysis. The analysis material is part of the official documents of the stricto sensu graduate programs of the Federal University of Sergipe - UFS, the CAPES assessment documents, the INEP data, as well as specific legislation dealing with post- graduation course in Brazil. The research showed that more than half of the programs of the UFS contemplate in their objectives the formation for the higher teaching, and since they have this purpose, they can be said that they constitute as places of teacher training. However, when we analyzed other elements indicative of formation, we found that 63% of these do not have subjects or obligatory activities in the completion of the studies as a condition for titling their students, which leads us to question the conception of teacher training for these programs, and in what way it is effectively carried out by them. The offer of at least one didactic-pedagogical discipline or activity in a mandatory way, was only proven in half of the doctoral courses, and in 37.5% of the masters courses, making them possible training territories, since the of these components evidences a presumption of authority. It was also evidenced that only 25% of UFS 'stricto sensu postgraduate programs, in their historical pathways, have advanced in their curricular components, as far as pedagogical training for the higher teaching is concerned, since they were created.